Biosynthesis of amino acid functionalized silver nanoparticles for potential catalytic and oxygen sensing applications. Issue 1 (12th December 2017) - Chandra, Abhishek; Singh, Man
Abstract : A green approach to the biosynthesis of amino acid functionalized silver nanoparticles (AgNPs) using Neem gum is reported herein. Abstract : A green approach to the biosynthesis of amino acid functionalized silver nanoparticles (AgNPs) using Neem gum is reported herein. To the best of our knowledge, this is the first attempt at biosynthesizing AgNPs. The AgNPs show good colloidal stability with surfactants and dyes. The reduction of Methylene blue (MB) by SnCl2 in micellar media, and Congo red/4-nitrophenol by NaBH4 validate the high catalytic efficiency of the AgNPs. This is the first report, as far as we know, on a detailed kinetic study of AgNPs catalyzed MB reduction in cationic, anionic and nonionic micellar media. The highest MB reduction rate was observed in anionic micellar medium with tryptophan functionalized AgNPs. The AgNPs were responsible for the backward oxidation of reduced MB in acidic nonionic micellar medium, which is the first ever demonstration of a one-cycle redox MB clock reaction involving silver nanoparticles. The clock reaction elucidated the potential use of the AgNPs as low-cost sensors for oxygen leakage in vacuum-packed food packages, and for creating an oxygen deficient environment in acidic aqueous and micellar media, where catalyst poisoning by O2 prevails. The deactivation of the catalytic activity of tryptophan functionalized AgNPs observed during the Congo red and 4-nitrophenol reduction may find application in catalytic reduction where improved selectivity is required. With the possibility of the large-scale production of the AgNPs on an economic platform, the AgNPs may thus hold great promise in effective and eco-friendly wastewater treatment, with potential application in oxygen sensing.